2013
DOI: 10.1093/cid/cit227
|View full text |Cite
|
Sign up to set email alerts
|

Breast Milk as a Possible Route of Vertical Transmission of Dengue Virus?

Abstract: We report a case of vertical transmission of dengue infection. The virus was detected and quantified by reverse-transcription polymerase chain reaction in sequential blood samples from mother and child as well as in breast milk, but not in cord blood. This case poses questions about the risk of breastfeeding transmission of dengue virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
79
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 9 publications
0
79
0
5
Order By: Relevance
“…The finding that RT-PCR on Newborn 2's serum was positive the day following the start of breast feeding can reasonably exclude this route of contamination for this infant. The ZIKV RNA load reported in the two breast milk samples (2.9 × 10 4 and 205 × 10 4 copies /mL) were higher than the DENV RNA load reported in a suspected case of DENV breast milk transmission (>0.01 × 10 4 and >0.1 × 10 4 copies /mL) in New Caledonia in 2012 [14]. Of interest, CHIKV RNA was not detected from 20 milk samples collected from breastfeeding viraemic mothers during an outbreak of CHIKV infection in Réunion Island in 2005-06 [16].…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The finding that RT-PCR on Newborn 2's serum was positive the day following the start of breast feeding can reasonably exclude this route of contamination for this infant. The ZIKV RNA load reported in the two breast milk samples (2.9 × 10 4 and 205 × 10 4 copies /mL) were higher than the DENV RNA load reported in a suspected case of DENV breast milk transmission (>0.01 × 10 4 and >0.1 × 10 4 copies /mL) in New Caledonia in 2012 [14]. Of interest, CHIKV RNA was not detected from 20 milk samples collected from breastfeeding viraemic mothers during an outbreak of CHIKV infection in Réunion Island in 2005-06 [16].…”
Section: Discussionmentioning
confidence: 59%
“…Perinatal transmission of arbovirus has been reported for DENV [10][11][12][13][14], chikungunya virus (CHIKV) [15,16], West Nile virus (WNV) [17,18] and yellow fever virus (YFV) [19,20]. Breast milk transmission has been reported for DENV [14] and WNV [18] and has been suspected for the vaccine strain of YFV [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transmission of ZIKV via breastfeeding has not yet been observed [8], although the transmission of other flaviviruses via this route has been described previously [54,55]. The other suspected routes of ZIKV transmission include monkey bite, mucocutaneous exposure, organ transplantation or hemodialysis [56,57].…”
Section: Transmissionmentioning
confidence: 99%
“…The CDC examined blood donations in Puerto Rico between April 3 and June 11, 2016, using a nucleic acid test and found that 68/12,777 (0.5%) samples were positive for ZIKV. 29 Other flaviviruses such as dengue and West Nile viruses can be detected in breast milk, [30][31][32] and while there is evidence for the presence of ZIKV in breast milk, there is no clear evidence for transmission. During the 2013 outbreak in French Polynesia, 2 women gave birth to It is likely that ZIKV can be transmitted through blood transfusion, although the frequency of this remains unknown.…”
mentioning
confidence: 99%